The Role of Scout Extracurricular Activities On The Independence of Grade V Students At Bangkal 01 State Elementary School - Halimatus Sa'adah; Uli Nur Baeti; Sima Gendis Pradina; Dani Syahiran; Ovi Nur Baytin; Nur Fitriana Sri Pangestu (Universitas Nusantara PGRI Kediri, 2026)
Extracurricular activities are a school program that trains students to be independent from an early age. This independence is important because it is related to students' abilities to be responsible, manage their time, and make their own decisions. This study was conducted to describe how extracurricular activities play a role in shaping student independence at Bangkal 01 Public Elementary School. This study used a simple descriptive quantitative method with a 15-item questionnaire instrument to 15 students. Data were collected by distributing questionnaires to students participating in scouting activities. The analysis results showed that the level of student independence was high with an average percentage of 93%. The study shows that extracurricular activities have a positive impact on student independence. In addition, these activities also help students build self-confidence and practice problem-solving skills through direct experiences. Thus, the extracurricular program at Bangkal 01 Public Elementary School plays a significant role in supporting student independence.